Pulsed electromagnetic field prevents lumbar bone loss in orchiectomy mice without altering systemic iron metabolism - Yang, Jiancheng; Feng, Yan; Pan, Mingming; Zeng, Yuhong (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThe therapeutic efficacies of pulsed electromagnetic fields (PEMFs) for postmenopausal osteoporosis are well established; however, their effects on male osteoporosis remain uncertain. Osteoporosis development is often associated with dysregulation of systemic iron metabolism. This study aimed to investigate the therapeutic effects of PEMFs on orchiectomy (ORX)-induced osteoporosis in mice and determine whether the mechanism involves regulation of systemic iron metabolism.MethodsTwenty-four 10-week-old male C57BL/6J mice were divided into the sham, ORX, and ORX + PEMF groups (n = 8 each). The ORX + PEMF group received PEMF treatment (15 Hz, peak of 3.82 mT, 40 min/d for 2 months) starting 2 weeks post-surgery. The bone loss was assessed via micro-computed tomography, biomechanical testing, dynamic histomorphometry, and TRAP staining. The systemic iron metabolism was evaluated via Prussian blue staining, atomic absorption spectrometry, and serum ELISA (hepcidin, ferritin).ResultsPEMF treatment partially prevented ORX-induced bone loss in the lumbar spine, as evidenced by significant improvements in the microstructure and mechanical properties of the bone, along with partially restored bone formation and suppressed bone resorption compared to the untreated ORX mice. However, PEMF application showed no significant protective effects on the femoral bone microstructure or cortical parameters. Crucially, PEMF treatment did not alter the markers of systemic iron metabolism, meaning that no changes were observed in the tissue iron deposition, iron content, serum ferritin level, serum hepcidin level, or liver hepcidin expression.ConclusionPEMF therapy exerts site-specific protective effects against ORX-induced osteoporosis in the lumbar spine of male mice to partially restore bone formation and reduce resorption. This therapeutic efficacy is independent of any alterations in the systemic iron metabolism. The findings of this study support PEMF application as a potential physical therapy for male osteoporosis while highlighting the need for site-optimized strategies.